2010
DOI: 10.3109/10717544.2010.531061
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of targeting efficiency of Adriamycin hydrochloride magnetic microspheres

Abstract: The objective of this study was to prepare magnetic microspheres as a targeting drug delivery system and to specifically evaluate its targeting efficiency. The magnetic microspheres were prepared by emulsion cross-linking techniques. Targeting efficiency was specifically investigated by experiments of biodistribution on rats and histological study. Adriamycin hydrochloride (ADR)-loaded magnetic microspheres were successfully prepared with the mean diameter of 3.853 μm (± 1.484 μm), and had its speciality of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…[1][2][3][4] However, researchers have reported that ADR demonstrates severe cardiac toxicity due to the poor specificity in reaching tumor tissue. To enhance tumor targeting, alleviate toxic side effects and improve the water solubility, nanospheres and microspheres, [5][6][7] liposomal systems, 8 and polymeric micelle systems 9,10 have demonstrated encouraging results to reduce cytotoxicity and increase the in vivo half-life. Out of the three systems mentioned above, the polymeric micelles have turned out to be one type of promising biomedical material which can be used in the development of an ADR delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, researchers have reported that ADR demonstrates severe cardiac toxicity due to the poor specificity in reaching tumor tissue. To enhance tumor targeting, alleviate toxic side effects and improve the water solubility, nanospheres and microspheres, [5][6][7] liposomal systems, 8 and polymeric micelle systems 9,10 have demonstrated encouraging results to reduce cytotoxicity and increase the in vivo half-life. Out of the three systems mentioned above, the polymeric micelles have turned out to be one type of promising biomedical material which can be used in the development of an ADR delivery system.…”
Section: Introductionmentioning
confidence: 99%